INTERVENSI GIZI PADA ANAK INDIKASI KURANG GIZI BERBASIS PANGAN LOKAL DI WILAYAH KAYU JATI TEMBILAHAN HULU : Gizi Kurang - SUHARNI, SUHARNI; Nurtanny, Nurtanny; Ardian, Roni (STIKes Hang Tuah Pekanbaru, 2025)
The focus on fulfilling children's nutrition is a serious concern for the government in efforts to eradicate nutritional problems in order to reduce nutritional problems. Referring to data from the Coordinating Ministry for Human Development and Culture, in Indonesia as of July 1, 2024, 36.10% of toddlers experienced nutritional problems, and 3.6 percent of them had problems and had to be intervened. Nutritional intervention through local food processing in the form of purple sweet potatoes (Ipomoea batatas L) and chayote (Sechium edule) is expected to be able to have an impact on improving nutrition in toddlers. This community service aims to provide nutritional intervention to children who are indicated as malnourished through local food processing. The intervention was given to children indicated as malnourished who live on Jl. Kayu Jati Tembilahan Hulu, Inhil Riau. During the intervention, the child was given a variety of local food processing for 4 (four) weeks with an interval of 1 (one) time per week. The results of the intervention showed a change in initial body weight from 12.20 kg to 12.55 kg. The intervention of providing additional food was carried out for 4 (four) weeks with a provision interval of 1 (one) time per week. Abstrak Fokus pemenuhan gizi terhadap anak-anak menjadi perhatian serius pemerintah dalam upaya pengentasan masalah gizi guna menekan masalah gizi. Merujuk data Kemenko PMK bahwa di Indonesia per 1 Juli 2024 ditemukan 36,10 % balita mengalami masalah gizi, dan 3,6 persen diantaranya bermasalah dan harus diintervensi. Intervensi gizi melalui pengolahan pangan lokal berupa ubi ungu (Ipomoea batatas L) dan labu siam (Sechium edule) diharapkan mampu memberikan pengaruh terhadap perbaikan gizi pada balita. Pengabdian masyarakat ini bertujuan untuk memberikan intervensi gizi terhadap anak yang terindikasi kurang gizi melalui olahan pangan lokal. Intervensi diberikan pada anak terindikasi kurang gizi yang beralamat di Jl. Kayu Jati Tembilahan Hulu, Inhil Riau. Selama intervensi, anak tersebut diberikan variasi olahan pangan lokal selama 4 (empat) minggu dengan interval waktu pemberian 1 (satu) kali seminggu. Hasil intervensi tersebut memperlihatkan adanya perubahan berat badan awal 12,20kg menjadi 12,55kg. Intervensi pemberian makanan tambahan dilakukan selamat 4 (empat minggu) dengan interval waktu permberian 1 (satu) kali seminggu.